Analysis of internal load characteristics of damage cabin under near-field underwater explosion - Xingxing WU; Jianhu LIU; Jun WANG; Haikun WANG; Lunping ZHANG (Zhongguo Jianchuan Yanjiu)
ObjectiveThis research aims to investigate the internal load characteristics of damaged cabins under near-field underwater explosion.MethodLoadings including high-speed fragment velocity of damaged outer plates, quasi-static pressure loads caused by detonation products, and water jetting loads resulting from bubble instability were explored by combining numerical simulation and theoretical methods, which basesd on large-scale cabin segment model experiment subject to near-field underwater explosions. ResultsThe results indicate that the secondary high-speed fragment loads generated from outer plates in near-field underwater explosions still resist high speed, which could cause huge damage to internal cabin structures and equipment. A thoery method based on the modified Taylor flat plate theory was proposed to predict the velocity of high-speed fragments. A quasi-static pressure loading generated by exiting detonation products could result in overall large deformation and tearing at cabin boundary.For the first time, it was discovered that the damaged cabin could suffer secondary damage from high-speed water jets, and the formation of high-speed water jets mainly attributed to three factors: strong shock wave propagation, detonation product expansion, and residual bubble contraction instability.ConclusionThis study provides a significant basis for the assessment of internal cabin loads under near-field underwater explosions.